Isomorphic substitution of samarium for strontium in the Sr₅(VO₄)₃OH structure - Get`man, E.I.; Marchenko, V.I.; Loboda, S.N.; Yablochkova, N.V.; Plehov, A.L. (Functional Materials, 2007)
Using the X-ray phase analysis and IR spectrocopy, the isomorphic substitution of samarium for strontium according to the Sr²⁺+OH⁻->Sm³⁺+O²⁻ has been studied in a synthetic hydroxyapatite corresponding to the system composition Sr₅₋ₓSmₓ(VO₄)₃(OH)₁₋ₓOₓ (O≤x≤0.40). The solid solutions on the basis of strontium hydroxyapatites (synthesized at 800°C from solutions) have been established to be formed within limits 0<x<0.12. The crystals structure of the solid solutions obtained has been refined by the Rietveld method.